Second primary cancer after intensity-modulated radiotherapy for nasopharyngeal carcinoma: A territory-wide study by HKNPCSG. (December 2020) - Chow, James C.H.; Tam, Anthony H.P.; Cheung, Ka-Man; Lee, Victor H.F.; Chiang, Chi-Leung; Tong, Macy; Wong, Edwin C.Y.; Cheung, Alice K.W.; Chan, Sunny P.C.; Lai, Jessica W.Y.; Ngan, Roger K.C.; Ng, Wai-Tong; et al.
Highlights: Cancer risk in nasopharyngeal carcinoma survivors who underwent intensity-modulated radiotherapy was 90% higher than that in the general population. Significant excess cancer risks were observed for oral cavity, sarcoma, oropharynx, paranasal sinus, salivary gland, thyroid, skin and lung. Re-irradiation is an independent risk factor for in-field second primary cancer development. Second primary cancer represents a significant cause of late mortality among NPC survivors. Abstract: Objectives: Long-term risk of second primary cancer (SPC) after definitive intensity-modulated radiotherapy (IMRT) for nasopharyngeal carcinoma (NPC) remains unclear. This study aims to evaluate the risk, predictive factors and survival impact of SPC in a large territory-wide cohort of NPC survivors in an endemic region. Materials and Methods: In this multicenter study, consecutive NPC patients (n = 3166) who underwent definitive IMRT in all six public oncology centers in Hong Kong between 2001 and 2010 were included. SPC risks were quantified by standardized incidence ratios (SIRs) and absolute excess risks (AERs) estimated from corresponding age-, sex-, and calendar year-specific population cancer incidence data from the Hong Kong Cancer Registry. Predictive factors and SPC-specific mortality were analyzed. Results: Over a median follow-up period of 10.8 years, 290 cases of SPC were observed with a crude incidence of 9.2%. Cancer risk in NPC survivors was 90% higher than that in general population [SIR, 1.9; 95% confidence interval (CI), 1.7–2.2], with an AER of 52.1 (95% CI, 36.8–67.3) per 10, 000 person-years at risk. Significant excess cancer risks were observed for oral cavity, sarcoma, oropharynx, paranasal sinus, salivary gland, thyroid, skin and lung. Advanced age, smoking, hepatitis B status, and re-irradiation were independent predictive factors. SPC accounted for 9.4% of all deaths among NPC survivors during the study period, and 10-year SPC-specific mortality was 3.4%. Conclusions: Second cancer risk after IMRT was substantial among NPC patients. SPC impairs long-term survival, and close surveillance is warranted as part of survivorship care.